Monte Carlo Method in Atmospheric Acoustics; Lecture Notes in Engineering and Computer Science; Vol. 2 : Proceedings of the International MultiConference of Engineers and Computer Scientists 2016. IMECS 2016, 16-18 March, 2016, Hong Kong - Burkatovskaya Yu. B. Yuliya Borisovna; Belov V. V. Vladimir Vasiljevich; Krasnenko N. P. Nikolay Petrovich; Shamanaeva L. G. Lyudmila Grigorjevna; Khaustov P. A. Pavel Aleksandrovich (2016, 2016)
Title screen